2015
DOI: 10.1007/s00394-015-0917-y
|View full text |Cite
|
Sign up to set email alerts
|

Urinary phytoestrogens and cancer, cardiovascular, and all-cause mortality in the continuous National Health and Nutrition Examination Survey

Abstract: 2 AbstractPurpose: Experimental studies suggest that phytoestrogen intake alters cancer and cardiovascular risk. This study investigated the associations of urinary phytoestrogens with total cancer (n=79), cardiovascular (n=108), and allcause (n=290) mortality among 5,179 participants in the continuous National Health and Nutrition Examination Survey (1999Survey ( -2004.Methods: Urinary phytoestrogens were measured using high performance liquid chromatography with tandem mass spectrometric detection. Survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…The analysis of several cohorts studies, which evaluated the association between flavonoids intake and incidence or mortality from cardiovascular disease, revealed that small amounts of flavonoid-based PhyEs may lower the risk of coronary heart disease mortality (Petersin et al, 2012). The association between urinary PhyEs levels and cardiovascular mortality risk was also evaluated, and it was found that enterolignan urinary concentrations were associated with a reduced risk of death from cardiovascular disease, whereas an opposite association was found for urinary concentration of total isoflavones (Reger et al, 2015). These results are consistent with previously published results, which confirmed that enterolignan intake was correlated with elevated high-density lipoprotein (HDL) levels and reduced triglyceride concentrations in US adults (Penelalco et al, 2012).…”
Section: Natural Xenoestrogensmentioning
confidence: 99%
“…The analysis of several cohorts studies, which evaluated the association between flavonoids intake and incidence or mortality from cardiovascular disease, revealed that small amounts of flavonoid-based PhyEs may lower the risk of coronary heart disease mortality (Petersin et al, 2012). The association between urinary PhyEs levels and cardiovascular mortality risk was also evaluated, and it was found that enterolignan urinary concentrations were associated with a reduced risk of death from cardiovascular disease, whereas an opposite association was found for urinary concentration of total isoflavones (Reger et al, 2015). These results are consistent with previously published results, which confirmed that enterolignan intake was correlated with elevated high-density lipoprotein (HDL) levels and reduced triglyceride concentrations in US adults (Penelalco et al, 2012).…”
Section: Natural Xenoestrogensmentioning
confidence: 99%
“…Another study found an inverse association between urinary concentrations of total enterolignans and cardiovascular mortality and between urinary concentrations of both total enterolignans and enterolactone and all-cause mortality [65]. Interestingly, this study also found a direct association between urinary concentration of total isoflavones and daidzein and risk of death from cardiovascular disease and all causes [65]. …”
Section: Discussionmentioning
confidence: 66%
“…Also, another study carried with US NHANES 2001–2010, found an inverse association between urinary enterolactone levels and obesity, waist circumference, serum triacylglycerols (TAG) levels, fasting glucose levels, fasting insulin levels and metabolic syndrome in adult males, and a direct association with high-density lipoprotein HDL-cholesterol levels [64]. Another study found an inverse association between urinary concentrations of total enterolignans and cardiovascular mortality and between urinary concentrations of both total enterolignans and enterolactone and all-cause mortality [65]. Interestingly, this study also found a direct association between urinary concentration of total isoflavones and daidzein and risk of death from cardiovascular disease and all causes [65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations